ANALISIS BAURAN PEMASARAN SEKTOR PARIWISATA PAHLAWAN STREET CENTER SEBAGAI DESTINASI WISATA NON ALAM DI KOTA MADIUN - Utami, Sri; Yolanda, Aisyah (PARADIGMA: Jurnal Ilmu Administrasi, 2025)
This research aims to analyze the marketing mix strategy for the Pahlawan Street Center (PSC) tourism sector as a non-natural tourism destination in Madiun City. Tourism is a strategic sector that plays an important role in economic growth, especially in increasing regional income and reducing unemployment. Madiun City, with limited land and no natural tourism, is developing PSC as a unique non-natural tourist attraction that has great potential. However, until now, PSC is still little known to tourists from outside the region. This research uses the marketing mix strategy concept (Marketing Mix) which consists of 9Ps: Product, Price, Place, Promotion, Political Power, Public Relations, Process, People, and Physical Evidence according to Boom and Bitner (2007). The aim of this research is to identify how the marketing mix strategy is implemented in PSC and the factors that hinder and support its implementation. The research results show that the marketing mix strategy at PSC still requires optimization, especially in the aspects of promotion and public relations to increase awareness and attraction of tourists to PSC. The main inhibiting factors are limited land and ineffective promotion, while government support and the potential for attractive icons from PSC are the main supporting factors. With the right marketing strategy, PSC can develop into a better known non-natural tourist destination and attract more tourists, which will ultimately have a positive impact on the regional economy of Madiun City.